Determination of the effects of different storage conditions and chemical treatments affecting protein profile and allergenicity of Cerithidea obtusa - Siti Rukaiyah Abd Fatah (Tanjong Malim, 2019)
Determination of the effects of different storage conditions and chemical treatments affecting protein profile and allergenicity of Cerithidea obtusa by Siti Rukaiyah Abd Fatah